IMPLEMENTATION OF THE PARIS AGREEMENT IN INDONESIA CASE STUDY: THE CLIMATE VILLAGE PROGRAM IN THE TOBEK GODANG SUB-DISTRICT - Adinda Salsabila Fitriandi; Yessi Olivia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT This research analyzes the Implementation of the Paris Agreement in Indonesia through the Climate Change Village Program. The case study in Proklim in Tobek Godang Village, Pekanbaru. This research will look at how the influence of Indonesian national policies and stakeholders on climate change and public views and understanding of the community about the importance of protecting the environment from an active community movement itself. This research uses a qualitative method that aims to explain how the implementation of the climate village program policy in Tobek Godang Village uses the perspective of Green Political. Data collection techniques in this research used primary data through interviews with three informants that are lurah, DLHK, and public and used document analysis. The results of this study indicate that the role of the local government through the implementation of Proklim in the Tobek Godang Village is very much needed to mobilize the community and is also very important for implementing national policies related to climate change mitigation and adaptation. However, in its implementation in the Tobek Godang Village there were several obstacles in the form of a lack of public awareness and funding. Even so, Proklim has contributed a lot by having a positive impact on reducing greenhouse gas emissions, reducing flooding, and increasing temperatures in the Tobek Godang Village area. Keywords: Environmental Policy Implementation, Paris Agreement, the Climate Change Village Program, Greenhouse Gas Emissions, Adaptation and Mitigation, Climate Change.